2020
DOI: 10.1002/ana.25756
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Therapy or IV Thrombolysis in Minor Stroke with Large Vessel Occlusion

Abstract: Objective Whether bridging therapy (intravenous thrombolysis [IVT] followed by endovascular treatment) is superior to IVT alone in minor stroke with large vessel occlusion (LVO) is unknown. Methods Multicentric retrospective observational study including, in intention‐to‐treat, consecutive IVT‐treated minor strokes (National Institutes of Health Stroke Scale [NIHSS] ≤ 5) with LVO, with or without additional mechanical thrombectomy. Propensity‐score (inverse probability of treatment weighting) was used to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 33 publications
3
84
0
1
Order By: Relevance
“…14 Trials are underway to test the effectiveness of thrombectomy in patients with large-artery occlusion and NIHSS scores 0–5 (In Extremis/Minor Stroke Therapy Evaluation [MOSTE; NCT 03796468], Endovascular Therapy for low NIHSS Ischemic Strokes [ENDOLOW; NCT 04167527]). In addition, two recent multicentre observational studies suggest a potential beneficial effect of IVT 118 and bridging therapy 119 in acute ischaemic stroke patients with minor stroke (NIHSS-scores < 6) and large vessel occlusion.
Expert consensus statement For patients with acute minor, non-disabling ischaemic stroke of < 4.5 h duration, and with large-vessel occlusion, 6 of 8 group members suggest intravenous thrombolysis with alteplase. One group member (WW) did not vote or comment on this chapter because he has been involved in the data monitoring committee of a trial related to this topic (TEMPO-2).
…”
Section: Resultsmentioning
confidence: 99%
“…14 Trials are underway to test the effectiveness of thrombectomy in patients with large-artery occlusion and NIHSS scores 0–5 (In Extremis/Minor Stroke Therapy Evaluation [MOSTE; NCT 03796468], Endovascular Therapy for low NIHSS Ischemic Strokes [ENDOLOW; NCT 04167527]). In addition, two recent multicentre observational studies suggest a potential beneficial effect of IVT 118 and bridging therapy 119 in acute ischaemic stroke patients with minor stroke (NIHSS-scores < 6) and large vessel occlusion.
Expert consensus statement For patients with acute minor, non-disabling ischaemic stroke of < 4.5 h duration, and with large-vessel occlusion, 6 of 8 group members suggest intravenous thrombolysis with alteplase. One group member (WW) did not vote or comment on this chapter because he has been involved in the data monitoring committee of a trial related to this topic (TEMPO-2).
…”
Section: Resultsmentioning
confidence: 99%
“…The MINOR‐STROKE collaboration retrospectively collected the data from all consecutive acute stroke patients admitted to 45 French stroke centers between 2006 and 2018 who fulfilled the following criteria [11]: (i) baseline admission National Institutes of Health Stroke Scale (NIHSS) score ≤5; (ii) large vessel occlusion on pre‐treatment vascular imaging [internal carotid artery (ICA), first or second segment of middle cerebral artery (MCA), basilar artery] and (iii) treated with IVT (alteplase only), with or without additional EVT. The present study focuses on patients with iICAo intended for IVT alone, including those who eventually received rescue EVT because of post‐IVT END.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies also showed that bridging therapy was associated with significant higher rate of any hemorrhage. 14, 15 This may have contributed to the outcomes of our patients.…”
Section: Discussionmentioning
confidence: 88%